Long chain arabinoxylans shift the mucosa-associated microbiota in the proximal colon of the simulator of the human intestinal microbial ecosystem (M-SHIME). (May 2017) - Truchado, Pilar; Hernandez-Sanabria, Emma; Salden, Bouke N.; Van den Abbeele, Pieter; Vilchez-Vargas, Ramiro; Jauregui, Ruy; Pieper, Dietmar H.; Possemiers, Sam; Van de Wiele, Tom
Highlights: LC-AX modulated lumen and mucus microbiota of proximal colon (M-SHIME). LC-AX modulated gut microbiota, consistent with inter-individual variations. LC-AX increased Bifidobacterium in both lumen and mucus compartments from M-SHIME. LC-AX had a potential prebiotic effect in the mucus layer. High dose of LC- AX increased propionate in the in vitro proximal colon. Abstract: Prebiotic compounds aim at improving human health by targeting beneficial gut microbes. We used a dynamic in vitro model of the human digestive tract (M-SHIME®) to study the modulatory effects of long-chain arabinoxylans (LC-AX) towards luminal and mucosal microbiota. Two doses (3 and 6 g/L) of LC-AX were supplied to the proximal colon compartments of the M-SHIME, three times per day for 3 days. Next generation sequencing and multivariate statistical analysis revealed the distribution of key microbial genera across M-SHIME compartments. Supplementation of 6 g/L of LC-AX significantly increased the relative abundance of Bifidobacterium in both lumen (from 0.34% to 0.41%, 1.2-fold) and mucus (from 0.14% to 0.29%, 2.1-fold) compared with the control ( P  < 0.001). Propionate (1.4-fold), as well as activity of β-xylanase, β-xylosidase and α-arabinofuranosidase ( P  < 0.05) were also increased in the lumen. LC-AX may potentially benefit host health by stimulating Bifidobacterium abundance and its metabolic activity.